Translation, cultural adaptation and validation of the Chinese version of the Carer Support Needs Assessment Tool for family caregivers of cancer patients receiving home-based hospice care - Sijia Zhou; Qianqian Zhao; Huimin Weng; Ning Wang; Xia Wu; Xinxin Li; Lili Zhang (BMC Palliative Care, 2021)
Abstract Background Family caregivers need to be supported in caring for patients at the end of life, but practical tools to assess their support needs have been missing in China. So this study aimed to culturally adapt and validate the Carer Support Needs Assessment Tool (CSNAT). Methods Cross-cultural adaptation of the original CSNAT for a Chinese setting was performed according to Brislin’s translation guidelines. A pilot study was conducted with 15 Chinese family caregivers of cancer patients receiving hospice home care and 5 medical staff. A cross-sectional survey of 205 family caregivers was conducted from December 2018 to May 2019 at a home-based hospice care institute in Shenzhen, China. The validation procedure comprised the establishment of (1) content validity by a group of six experts; (2) face validity by 15 family caregivers; (3) criterion validity by calculating Spearman’s correlations between the CSNAT and caregiving burden, caregiving preparedness and quality of life scales; (4) internal consistency using Cronbach’s alpha. Results The CSNAT demonstrated good face validity and good content validity. CSNAT scores showed clear positive correlations with caregiving burden and negative correlations with preparedness for caregiving and quality of life. Internal consistency was high (Cronbach’s alpha = 0.899), although such reliability testing is not recommended for this tool. Conclusions The Chinese version of the CSNAT is a valid tool that is appropriate for identifying needs of family caregivers of cancer patients in home-based hospice care.